2020
DOI: 10.1101/2020.05.17.100933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thiazoline-related TRPA1 agonist odorants orchestrate survival fate in mice

Abstract: TFO-induced strong crisis perception maximizes latent life-protective effects by shifting metabolism to a crisis response mode characterized by hypothermia, hypometabolism and crisis immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…We compared the 2MT-induced thermoregulatory response between wild-type and Trpa1 -/mice using a behavior paradigm as previously described 33,35 . To study the effect of 2MT on the change of body temperature, we used infrared (IR) thermography combined with implanted telemetry transmitter to measure in real time the cutaneous and core body temperature, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We compared the 2MT-induced thermoregulatory response between wild-type and Trpa1 -/mice using a behavior paradigm as previously described 33,35 . To study the effect of 2MT on the change of body temperature, we used infrared (IR) thermography combined with implanted telemetry transmitter to measure in real time the cutaneous and core body temperature, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because Sp5 neurons also project to PB 66,67 , we believe that a subpopulation of vGlut2 + PBel neurons receive the 2MT-evoked innate fear signal directly from TG or indirectly via Sp5 neurons. Once activated, these vGlut2 + PBel neurons transmit the signal to Interestingly, Matsuo and colleagues found that chemogenetic activation of the NTS-PB pathway could also induce hypothermia 35 , suggesting the potential existence of a PB-PSTh-NTS-PB feedforward loop for 2MT-evoked hypothermia. Furthermore, they also reported that trigeminal, vagal, or olfactory ablation could partially suppress 2MT-evoked hypothermia 62 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations